Development Of Intercultural Competence To Improve Communicative Processes Through Content-Based Instruction Activities (2017)
This work aims the presentation of relevant information related to design and implementation of a methodological proposal to develop intercultural competence as a facilitator of communication processes in students of grade 1105E of the Mercedes Nariño School, in the program Media Fortalecida. This purpose was carried out through the elaboration and implementation of a set of activities that were structured taking into account Content-Based Instruction (CBI) features; it is a teaching method from the communicative approach for teaching English as a foreign language. To achieve that purpose, was carried out a process that took into account the stages of identification of the difficulty, design and implementation of the proposed activities and evaluation of the proposal.